Análise do modus vivendi e da sociabilidade de comunidades tradicionais frente aos impactos das mudanças climáticas globais: estudo de caso da comunidade tradicional de geraizeiros da Matinha (Guaraí/TO) - Campos, Alexandre de Castro [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This research sought to contribute to a theoretical field that is currently being structured on traditional Amazonian communities and socio-environmental relations in the face of the impacts of global climate change. In this sense, its general objective was to analyze the modus vivendi and sociability of the traditional community of geraizeiros from Matinha (Guaraí/TO), based on the impacts caused by global climate change. It takes a qualitative, descriptive approach, focusing on the complex dynamics of community development and adopting the case study as its central method of investigation. The traditional community of geraizeiros from Matinha, in the Brazilian legal Amazon, was taken as the object of study, intentionally and nonprobabilistically, given its strong traditional and cultural relationship with its territory, as well as the impacts of climate change on the community. The main results obtained from the community reveal socio-environmental perceptions and experiences directly impacted by climate change in the region. In the interviews, residents reported increasingly irregular and decreasing rainfall, rising temperatures and more frequent outbreaks of fire. These factors have had a significant impact on agricultural practices and local extractivism, requiring adaptations in cultivation techniques and soil management. Changes in the traditional planting and harvesting periods were mentioned, as well as a reduction in agricultural productivity, highlighting the need for resilience strategies in the face of ongoing environmental transformations. It was concluded that this doctoral thesis contributes to the debates on the subject and also to the structuring of public policies and their socio-environmental indicators in the face of the impacts of climate change on traditional communities, especially those located in the Brazilian Amazon.
Analysis of the modus vivendi and sociability of traditional communities in the face of the impacts of global climate change: a case study of the traditional Geraizeiros community of Matinha (Guaraí/TO)
Keywords: Comunidades tradicionais; Amazônia legal; Mudança do clima; Socioambiental